2011
DOI: 10.1016/j.ejphar.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Large conductance Ca2+-activated K+ channel activation with NS1619 decreases myogenic and neurogenic contractions of rat detrusor smooth muscle

Abstract: Large conductance voltage- and Ca2+-activated K+ channels are important in regulating detrusor smooth muscle (DSM) function. Here, we examined systematically how the BK channel pharmacological activation modulates DSM contractility. NS1619, a potent BK channel activator, was utilized as a pharmacological tool to investigate the effect of BK channel activation on rat DSM contractility. Isometric tension recordings of DSM strips isolated from rat urinary bladder were performed systematically under various experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 40 publications
4
34
1
Order By: Relevance
“…This decrease of intracellular Ca 2ϩ is caused by activation of the BK channel, membrane hyperpolarization, and subsequent inhibition of the L-type voltage-gated Ca 2ϩ channels. These findings are also supported by earlier studies showing that NS-1619 decreases rat and guinea pig DSM contractility by activation of the BK channel and inhibition of L-type voltage-gated Ca 2ϩ channels (36,38).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This decrease of intracellular Ca 2ϩ is caused by activation of the BK channel, membrane hyperpolarization, and subsequent inhibition of the L-type voltage-gated Ca 2ϩ channels. These findings are also supported by earlier studies showing that NS-1619 decreases rat and guinea pig DSM contractility by activation of the BK channel and inhibition of L-type voltage-gated Ca 2ϩ channels (36,38).…”
Section: Discussionsupporting
confidence: 79%
“…NS-1619 (EC 50 ϭ 10 -30 M) decreases contractility in guinea pig DSM by activation of the BK channel (36). Our recent study revealed that BK channel activation with NS-1619 significantly inhibits spontaneous, pharmacologically induced and nerve-evoked contractions in rat DSM (38). However, functional studies performed on human DSM specimens have not addressed the role of BK channel pharmacological activation under normal physiological conditions of spontaneous activity but rather after DSM depolarization with KCl (31).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In ion efflux in vitro assays, EC50 for BK has reported to be in 1-4 mM range for NS1619 and NS-8 (Parihar et al, 2003b). Most data reporting the specificity of these molecules have been generated in functional studies where a dependency on BK activation in the NS-8-or NS1619-induced effects is abolished by BK-selective toxins (Holland et al, 1996;Malysz et al, 2004;Soder and Petkov, 2011). Although NS-8 is a known activator of BK (Parihar et al, 2003b;Malysz et al, 2004), NS1619 is considered to be the only selective BK opener by some authors (Ghatta et al, 2006) without any effect on KATP, voltage-gated K + , Na + or Ca 2+ channels (Olesen et al, 1994).…”
Section: Figurementioning
confidence: 99%